2006
DOI: 10.1111/j.1365-2621.2005.tb07191.x
|View full text |Cite
|
Sign up to set email alerts
|

Oat-based Symbiotic Beverage Fermented by Lactobacillus plantarum, Lactobacillus paracasei ssp. casei, and Lactobacillus acidophilus

Abstract: : Oats and probiotics have long been recognized for their health benefits. The objectives of this study were (1) to study the ability of Lactobacillus plantarum (B‐28), Lactobacillus paracasei ssp. casei (B‐29) isolated from a traditional Bulgarian cereal‐based fermented beverage, and Lactobacillus acidophilus from Chr. Hansen, Milwaukee, Wis., U.S.A., to remove cholesterol from the media and to adhere to the Caco‐2 cell line, (2) to optimize the fermentation conditions to develop a beverage using these probi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 28 publications
4
38
0
1
Order By: Relevance
“…With regards to the fermentation time, much longer is usually needed than during standard cow milk yogurt production, since potential probiotic bacteria (type of bacteria currently chosen to develop these foodstuffs due to the added value on the final product) have more complex nutritional requirements (Severson, 1998), especially when growing in vegetable matrices. The reported fermentation times have been found to be around 16-24 h if no growth enhancers are used in the formulation (Dimitris Charalampopoulos & Pandiella, 2010;D Charalampopoulos, Pandiella, & Webb, 2002;Coda, Rizzello, & Gobbetti, 2010;Correa, Castro, & Saad, 2008;Blaiotta, Di Capua, Coppola, & Aponte, 2012;Cui, Chen, Wang, & Han, 2013;Gokavi et al, 2005;Gupta, Cox, & Abu-Ghannam, 2010;Martensson, Oste, & Holst, 2002). The fermentation procedure finishes when the pH value of milks reaches 4.2-4.5.…”
Section: Processing Of Fermented Vegetable Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the fermentation time, much longer is usually needed than during standard cow milk yogurt production, since potential probiotic bacteria (type of bacteria currently chosen to develop these foodstuffs due to the added value on the final product) have more complex nutritional requirements (Severson, 1998), especially when growing in vegetable matrices. The reported fermentation times have been found to be around 16-24 h if no growth enhancers are used in the formulation (Dimitris Charalampopoulos & Pandiella, 2010;D Charalampopoulos, Pandiella, & Webb, 2002;Coda, Rizzello, & Gobbetti, 2010;Correa, Castro, & Saad, 2008;Blaiotta, Di Capua, Coppola, & Aponte, 2012;Cui, Chen, Wang, & Han, 2013;Gokavi et al, 2005;Gupta, Cox, & Abu-Ghannam, 2010;Martensson, Oste, & Holst, 2002). The fermentation procedure finishes when the pH value of milks reaches 4.2-4.5.…”
Section: Processing Of Fermented Vegetable Milkmentioning
confidence: 99%
“…Some additives are frequently introduced into the vegetable matrix, mainly sugars and prebiotics (as growth enhancers), to promote the viability of bacteria and to reduce the length of the fermentation process (in order to avoid crosscontamination problems). Mono and oligosaccharides, some prebiotics such as inulin, β-glucans and dietary fibers have been the growth enhancers most commonly used by different authors (Akalin, Tokusoglu, Gonc, & Aycan, 2007;Gokavi, Zhang, Huang, Zhao, & Guo, 2005;Ozer, Akin, & Ozer, 2005;Rosburg, Boylston, & White, 2010;Sendra et al, 2008). Potentially, prebiotics are naturally present in both cereals and nuts (i.e.…”
Section: Processing Of Fermented Vegetable Milkmentioning
confidence: 99%
“…Beta-glucan has also been found to aid in enhancing the human immune system's response to bacterial infection (Coman et al, 2013). Studies which tested fermented dairy products containing oat flour mainly found that the beta-glucan increased the microbial count of different Lactobacillus probiotic strains (Angelov et al, 2006;Coman et al, 2013;Gokavi et al, 2005;Kedia et al, 2008;Lazaridou et al, 2014;Luana et al, 2014;Singh et al, 2012). …”
Section: Oatmentioning
confidence: 99%
“…Oats are a source of dietary fiber that have been found to reduce the risk of certain cancers, decrease constipation, lower cholesterol, and control diabetes (Gokavi et al, 2005). Oat bran contains the fiber beta-glucan which contributes to health benefits such as reducing the risk of cardiovascular disease and stroke (Coman et al, 2013;Lazaridou et al, 2014).…”
Section: Oatmentioning
confidence: 99%
See 1 more Smart Citation